The study of feasibility and acceptability of using HIV self-tests in high-risk Iranian populations (FSWs, MSM, and TGs): a cross-sectional study - Ghobad Moradi; Elnaz Ezzati Amini; Azam Valipour; Katayoon Tayeri; Parvin Afsar Kazerooni; Leila Molaeipour; Yousef Moradi (BMC, 2022)
Abstract Background This study aimed to evaluate the feasibility of using the HIV self-test in high-risk Iranian groups (MSM, FSWs, and TGs). Methods This study was a mixed study designed as a quantitative-qualitative study conducted between October 1, 2020, and June 22, 2021, in Tehran and Karaj, Iran. The sample size needed for this study generally was 1000 people, including FSWs, MSM, and transgender individuals. Convenience and snowball sampling methods were used to collect the samples. Results A total of 930 eligible respondents were enrolled in the study, of whom 456 (49%) were female and 49 (5.3%) were transgender (98% of TGs were male to female), and their mean age was 33.63 years (10.54 SD). The feasibility of using HIV self-tests in Iranian high-risk groups was significantly high. The majority of participants (97%) did not have any confidentiality problems while preparing or performing the test. In general, feasibility was assessed based on five questions. The overall feasibility score was 6.33 (0.824 SD). Taking tests, reading HIV test results, finding a safe place to do the test, and accessing HIV self-tests showed a high average. Conclusion HIV self-testing was highly acceptable and feasible among high-risk populations, so routine HIV testing was efficiently possible.